2009
DOI: 10.1016/j.applthermaleng.2009.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of nanofluids forced convection in circular tubes

Abstract: In this paper, developing laminar forced convection flow of a water-Al 2 O 3 nanofluid in a circular tube, submitted to a constant and uniform heat flux at the wall, is numerically investigated.A single and two-phase model (discrete particles model) is employed with either constant or temperaturedependent properties. The investigation is accomplished for size particles equal to 100 nm. The maximum difference in the average heat transfer coefficient between single and two phase models results is about 11%.Conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
185
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(218 citation statements)
references
References 50 publications
15
185
0
2
Order By: Relevance
“…This is due to the increase of the Prandtl number of the nanofluid and also to an increase in volume fraction. Here, the results are similar to that observed by Bianco et al 19 and He et al 21 . The figures show the increase of the Cu content in the nanofluid instead of the CuO tends to increase the heat transfer coefficients for the same volume fraction nanofluid.…”
Section: Enhancement Of Heat Transfer With Monocularsupporting
confidence: 93%
See 2 more Smart Citations
“…This is due to the increase of the Prandtl number of the nanofluid and also to an increase in volume fraction. Here, the results are similar to that observed by Bianco et al 19 and He et al 21 . The figures show the increase of the Cu content in the nanofluid instead of the CuO tends to increase the heat transfer coefficients for the same volume fraction nanofluid.…”
Section: Enhancement Of Heat Transfer With Monocularsupporting
confidence: 93%
“…The results obtained for each particular test case showed that for the tube flow problem under consideration, the 757,817 elements appeared to be satisfactory to ensure the precision of the numerical results as well as their independency with respect to the number of nodes used. The computer model was successfully validated with correlations reported by Shah 2006 19 for thermally and hydraulically developing flow, which showed an average error of less than 2 , as reported in Fig. 2 and Fig.…”
Section: Heat Transfer Enhancement Calculation Processsupporting
confidence: 58%
See 1 more Smart Citation
“…Figure 5b shows Nu as a function of flow rate at the nanoparticle volume fraction of 1 % in both experimental (previous work) and CFD (current work), with maximum difference between the experiment and numerical results of 9 %. The difference could be caused by some factors such as particle size, which effect on the viscosity, temperature dependant properties and the Brownian motion of the particles which effect on the thermal conductivity [38][39][40]. Comparison between the experimental Nu from [28] and the predicted Nu from [37].…”
Section: 2-validation Of the Cfd Modellingmentioning
confidence: 99%
“…For example, Mehrez et al [15] numerically investigated the entropy generation and the mixed convection heat transfer of copper/water-based nanofluids in an inclined open cavity with uniform heat flux at the wall. During the last decade, many other authors compared the performance of the different single and two-phase models with constant or temperature-dependent properties in the context of nanofluid flows [16][17][18][19][20][21]. A detailed state-of-the-art review has been besides recently proposed by Kakaç and Pramuanjaroenkij [10].…”
Section: Introductionmentioning
confidence: 99%